'The roar that lies on the other side of silence': supporting aspiring teachers in developing dissonance, uncertainty, and compassion for diverse learners. Issue 4 (2nd October 2019) - Gomez, Mary Louise; Johnson Lachuk, Amy
ABSTRACT: In this text, we examine ways teacher educators might inspire: compassion in aspiring teachers for students with whom they interact, and dissonance and uncertainty concerning ways they talk and think about them. These activities primarily fall into two categories: (1) working in schools where large numbers of children differing from themselves in race, language background, and socioeconomic status attend, and (2) offering multiple opportunities for students to critically talk about their interactions with children and families. Through these experiences, guided by their teacher educators, we hope university students will develop critical reflection on their own and others' practices.